Effect of Astaxanthin Cream on MMP-1 and SOD Expression in Wistar Rats Exposed to ultraviolet B - Rachmawati, Nita; Pertiwi, Danis; Thomas, Siti (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Ultraviolet B (UVB) exposure is the main cause of skin damage leading to photoaging, increasing Reactive Oxygen Species (ROS) and triggering the production of Matrix metalloproteinase-1 (MMP-1) enzymes that play an important role in photoaging, describing clinical signs including wrinkles, thickening, dryness and pigmentation. Astaxanthin can inhibit ageing and reduce wrinkles, has strong antioxidant potential that can neutralize ROS, and suppress MMP-1 activity. The purpose of this study was to determine the effect of astaxanthin cream on the levels of MMP-1 and Superoxide Dismutase (SOD) enzyme production in mouse skin tissue exposed to short-term UVB light experimental research with a post-test-only control group design. The experimental animals used were 28 Wistar rats divided into 4 groups, namely group K1 (healthy), group KN exposed to short-term UVB and given base cream, group P1 exposed to short-term UVB rays and given 0.05% astaxanthin cream, and group P2 exposed to short-term UVB rays and given 0.1% astaxanthin cream. The treatment was carried out for 5 days, and on the 6th day, the levels of MMP-1 enzyme production in skin tissue and SOD were examined using the immunohistochemical method. Based on One-way ANOVA, there was a significant difference in the average levels of MMP-1 enzyme production in the skin tissue of all groups (p = 0.000). The highest MMP-1 production was found in the KN group, while in the P2 group, the levels were lower and not significantly different from the healthy group (K1). Significant differences in SOD expression were also observed among all groups (p = 0.000) using the Kruskal-Wallis test. The highest SOD expression was found in group P2 and was significantly different from groups P1 and KN. Topical astaxanthin cream administration affected MMP-1 enzyme production in skin tissue and SOD expression in Wistar rats exposed to short-term UVB radiation. Astaxanthin-based cream formulation has the potential to be developed as a topical agent to prevent skin damage caused by sun exposure, and these findings require further validation through studies on human skin models or early clinical trials.